Emerging Economy Responses to the Global Financial Crisis of 2007-09 : An Empirical Analysis of the Liquidity Easing Measures - Yehoue, Etienne (Washington, D.C. : International Monetary Fund, 2009)
This paper draws on a unique data set on the nontraditional systemic liquidity easing measures recently undertaken by many emerging market economies. It offers an empirical analysis of the key determinants affecting the decision to undertake these measures over the period September 2008-March 2009. The paper finds that economy size, access to international credit markets, CDS spreads, currency depreciation, and current account balances are among the key factors influencing the adoption of these measures. It provides a rationale for the differences in central bank policy responses, which reflect differences in economic structures rather than conflicting views on fundamental principles. The paper also provides a preliminary assessment of the effectiveness of these measures and points out that despite their positive impacts, they have not fully shielded the real economy from the recent financial meltdown.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet